The Effects of Dietary Yucca Schidigera on Egg Yield Parameters and Egg Shell Quality of Laying Japanese Quails (Coturnix coturnix japonica) - Ayasan, Tugay; Yurtseven, Sabri; Baylan, Mikail; Canogullari, Sibel (International Journal of Poultry Science, 2005)
The present study was carried out to determine whether dietary Yucca schidigera powder would affect egg yield parameters and egg shell quality of laying Japanese quail (Coturnix coturnix Japonica). In this study, 30 female Japanese quails were used. The experimental quails were divided into two dietary treatment groups of similar mean weight comprising 30 birds each, which was divided into 3 subgroups of birds each. A standard layer feed, basal diet of the trial was supplemented with 0 or 120 ppm Yucca schidigera powder. Feed and water were supplied ad libitum and light was provided 16 hours (from 8.00 to 24.00) each day. Laying performance was determined daily by measuring feed intake, feed conversion efficiency (feed intake/egg weight), egg production (number and weight). Egg quality, length, width, shape index (width/length), shell weight, shell thickness of each egg obtained on the sixth days of every week were recorded. After measuring width and length, the egg was broken was then separated and then weighted. Shell samples from top, middle and bottom sites of the egg were measured for thickness using a micrometer and the mean was calculated prior to statistical analysis. The results obtained in this experiment showed that Yucca schidigera supplementation to the diet tended to improve feed conversion efficiency, egg weight (P<0.05), while reducing egg shell thickness but not affected on feed intake, egg production, egg shell weight, egg shape index, number of eggs (42 days) (P>0.05).